The innovative exploration， establishment and application of Shanghai diarrhea comprehensive surveillance - GONG Xiaohuan; LIN Sheng; XIAO Wenjia; TENG Zheng; CHEN Min; ZHANG Xi; WU Huanyu; PAN Hao (Shanghai yufang yixue, 2022)
In order to meet the needs of prevention and control of intestinal infectious diseases， a comprehensive surveillance for diarrheal diseases has been innovated and explored in Shanghai since 2012. The surveillance has extensive distribution of sentinel hospitals， systematic sampling， multi-pathogen collection， and hospital information system （HIS） as the basis， which has achieved “One system for surveillance of multiple diseases and one sample for detection of multiple pathogens". Continual active surveillance for the whole population has been conducted， covering demography， clinical information， epidemiology， pathogen detection， and drug sensitivity test for diarrhea cases. The surveillance has obtained preliminary achievements as follows. First， diarrheal diseases and their periodic changes have been characterized， in which the most prevalent pathogen of diarrhea is determined to be norovirus in Shanghai. Second， some rare pathogens and serotypes have been identified that may provide clues to the sources of outbreaks. Third， it facilitates the information sharing between public health institutions and clinical institutions， and provides scientific evidence for clinical diagnosis and treatment. In the future， Shanghai diarrhea comprehensive surveillance will be improved for expanding range and depth of surveillance， artificial intelligence assisted diagnosis and treatment， early warning of outbreaks， prediction of epidemic trends， and application of new detection technologies.